A cautionary tale of hyperbilirubinaemia in subhepatic appendicitis - Gopakumar Hariharan; Manimegalai Shanmuganathan (James Cook University, 2021)
Subhepatic appendicitis is rare in children and often presents with atypical symptoms and signs, resulting in delayed diagnosis with attendant complications. The presence of hyperbilirubinemia could be a marker of complicated appendicitis and may assist rural physicians to seek specialist assistance early.